Curcumin and Glu-GNPs Induce Radiosensitivity against Breast Cancer Stem-Like Cells. (29th December 2020) - Yang, Ke; Liao, Zhiwei; Wu, Yujian; Li, Mengjie; Guo, Tingting; Lin, Jiayi; Li, Yanwu; Hu, Chenxia
Abstract : Breast cancer stem cells are an important cause of radiotherapy resistance in the clinical treatment of breast cancer patients. How to target breast cancer stem cells is the key to improving the efficacy of breast cancer radiotherapy. We proposed for the first time that curcumin combined with glucose nanogold particles (Glu-GNPs) targeted breast cancer stem cells to reduce radiotherapy resistance, which can significantly enhance the apoptosis level of MCF-7 and MDA-MB-231 breast cancer stem-like cells (BCSCs) after radiotherapy and antiproliferation and colony-forming. Under simulated hypoxic conditions, curcumin combined with Glu-GNPs can significantly improve the ROS level of MCF-7 and MDA-MB-231 mammospheres; reduce the expression of HIF-1 α and HSP90, thereby inhibiting the tumor cells' own stress ability; promote the apoptosis of tumor stem cells; and enhance the sensitivity of radiotherapy. The current results indicate that the combination of curcumin and Glu-GNPs has great potential to relieve tumor hypoxia and increase radiosensitivity on BCSCs, providing scientific research data for developing a novel radiosensitizer with high efficiency and low toxicity.